State and Local Probation and Parole Systems, 1976 ([Verlag nicht ermittelbar], 1984)
This study is a census of all state and local probation and parole systems. It was conducted in late 1976 by the United States Census Bureau for the Bureau of Justice Statistics. The data contain information on each agency, including jurisdiction, funding and operation, employment, and client caseload.